2020
DOI: 10.1074/jbc.ra120.015349
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific deacylation by ABHD17a controls BK channel splice variant activity

Abstract: S-acylation, the reversible post-translational lipid modification of proteins is an important mechanism to control the properties and function of ion channels and other polytopic transmembrane proteins. However, while increasing evidence reveals the role of diverse acyl protein transferases (zDHHC) in controlling ion channel S-acylation the acyl protein thioesterases that control ion channel deacylation are very poorly defined. Here we show that the α/β-hydrolase domain-containing protein 17a (ABHD17a) deacyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…ABHD17A (α/β-hydrolase domain-containing protein 17a) is another biomarker related to voltage channels. Previous research demonstrated that ABHD17A modulates ion channels at the post-transcriptional level by deacetylating the stressregulated exon domains of large conductance voltageand calcium-activated potassium channels [14]. Moreover, low expression of ABHD17A is associated with improved overall survival of PRCA according to survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…ABHD17A (α/β-hydrolase domain-containing protein 17a) is another biomarker related to voltage channels. Previous research demonstrated that ABHD17A modulates ion channels at the post-transcriptional level by deacetylating the stressregulated exon domains of large conductance voltageand calcium-activated potassium channels [14]. Moreover, low expression of ABHD17A is associated with improved overall survival of PRCA according to survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the STREX variant of the BK channel includes a CTD that is palmitoylated and modified by a distinct set of zDHHC proteins [ 90 ]. Adding to this complexity is the reversibility of palmitoylation at both the first intracellular loop and the C-terminal STREX domain, where depalmitoylation is mediated by distinct acylprotein thioesterases [ 89 , 91 ].…”
Section: Zdhhc : Protein Substrate Assignmentmentioning
confidence: 99%
“…Indeed, genetic knockdown of zDHHC23, or site-directed mutagenesis of Cys53 : 56 to alanine results in reduced cell surface expression and enhanced retention of the α-subunit in the endoplasmic reticulum [ 53 55 ]. The S0–S1 site is de-acylated by the thioesterases APT1 (Lypla1) and the related APT1-like thioesterase (Lyplal1) resulting in enhanced retention in the trans Golgi network [ 55 , 56 ]. Lyplal1 has been associated with type 2 diabetes [ 57 ] including through use of first-phase insulin secretion as a marker to identify candidate interacting SNPs [ 58 ].…”
Section: Insulin Secretionmentioning
confidence: 99%
“…An siRNA-based screen revealed the STREX insert is S-acylated by multiple zDHHCs including the plasma membrane localized zDHHC5 and Golgi located zDHHC17, with zDHHC17 being the major zDHHC controlling the STREX domain in HEK293 cells [ 63 , 64 ]. Conversely, STREX is almost exclusively de-acylated by the plasma membrane localized thioesterase ABHD17a (also by ABHD17c but not the related ABHD17b) [ 56 ]. Thus, STREX is S-acylated and de-acylated by distinct enzymes compared to those that control S-acylation of the conserved S0–S1 domain.…”
Section: Insulin Secretionmentioning
confidence: 99%